Impact of Corporate Social Responsibility on consumers: A case study of Kaufland Česká republika v.o.s. - Melníková, Jitka (My University, 2021)
During past years, topics of sustainability and corporate social responsibility (CSR) have noted an increasing interest by the society. As a result, an ever-rising number of organizations are get- ting engaged in the area of CSR. Existing studies have examined the awareness as well as interest in these phenomena. Moreover, the effects on consumers have been studied as well. However, a complex examination of the phenomenon of CSR and its influences is a scarce research area. Therefore, this research struggles to fill in the research gap and Is dedicated to the study of impacts of CSR on consumers while using a perspective of both company and consumers. In order to be able to answer the research question defined, four objectives were identified. The first objective aims to familiarize with the concept of sustainability and CSR. Secondly, to exam- ine the implementation of CSR activities and in addition, when using a case company as an aux- iliary tool. Thirdly, to investigate customer’s opinions and awareness of CSR policy and activities. The last objective is devoted to the evaluation of the impact of CSR activities on consumers. The empirical part of the study made use of both qualitative and quantitative research methods. The qualitative technique that was chosen was a semi-structured interview. To be more specific, two interviews were conducted, one with the CSR manager of the case company and second one with the CSR project manager of the sister company in Slovakia, offering an international over- view of CSR policy and activities. When it comes to the quantitative research, 105 respondents, mainly students were chosen as a sample. All the participants come from the Czech Republic since the case company studied is a Czech subsidiary of the German retail chain. The research conducted confirms that a CSR initiative does have an impact on consumers. However, this im- pact does not have to be always translated into purchase decisions. When it comes to the spe- cific effects of CSR on consumers, the research suggests firstly an increased reputation and im- age of the company, secondly increased loyalty to the company, thirdly formation of preference of the company over its competitors and lastly purchase of products made by the company. Additionally, CSR affects a perceived value of the company as well, to be more specific, socially committed companies are more valuable in the eyes of consumers. Nevertheless, it appears that a price, reputation and image of a company as well as a brand itself play a more significant role to consumers than the CSR.
Keywords: corporate responsibility; social responsibility; consumers; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business